Measurements of Four-Lepton Production at the Z Resonance in pp Collisions at s√=7 and 8 TeV with - Aad, G. (2014)
Measurements of four-lepton (4ℓ, ℓ=e,μ) production cross sections at the Z resonance in pp collisions at the LHC with the ATLAS detector are presented. For dilepton and four-lepton invariant mass regions mℓ+ℓ->5  GeV and 80